ABC transporters in fish species: a review - Ferreira, Marta; Costa, Joana; Reis-Henriques, Maria A. (Frontiers in Physiology, 2014)
ATP-binding cassette (ABC) proteins were first recognized for their role in multidrug resistance (MDR) in chemotherapeutic treatments, which is a major impediment for the successful treatment of many forms of malignant tumors in humans. These proteins, highly conserved throughout vertebrate species, were later related to cellular detoxification and accounted as responsible for protecting aquatic organisms from xenobiotic insults in the so-called multixenobiotic resistance mechanism (MXR). In recent years, research on these proteins in aquatic species has highlighted their importance in the detoxification mechanisms in fish thus it is of extreme added value to continue these studies. Several transporters have been pointed out as relevant in the ecotoxicological context associated to the transport of xenobiotics, such as P-glycoproteins (Pgps), multidrug-resistance-associated proteins (MRPs 1-5) and breast resistance associated protein (BCRP). In mammals, several nuclear receptors have been identified as mediators of phase I and II metabolizing enzymes and ABC transporters. In aquatic species, knowledge on co-regulation of detoxification mechanism is scarce and needs to be addressed. The interaction of emergent contaminants, with chemosensitizer potential, with ABC transporters in aquatic organisms can compromise detoxification processes and have population effects and should be studied in more detail. This review intends to summarize the recent advances in research on MXR mechanisms in fish species, focusing in 1) regulation and functioning of ABC proteins; 2) cooperation with phase I and II biotransformation enzymes; and 3) ecotoxicological relevance and information on emergent pollutants with ability to modulate ABC transporters expression and activity. Several lines of evidence are clear suggesting the important role of these transporters in detoxification mechanisms and must be further investigated in fish.